Analysis of Self-Regulated Learning at Each Level of Mathematical Creative Thinking Skill - Munahefi, Detalia Noriza; Kartono; Waluya, Budi; Dwijanto (Boletim de educação matemática BOLEMA, 2022)
Abstract Most individuals do not understand creative mathematical thinking only as a cognitive factor, whereas creative mathematical thinking plays a role in affective factors. Self-regulated learning is considered an affective factor that influences mathematical creative thinking skill. The purpose of this study determines the effect of SRL on mathematical creative thinking skill and analyzes in detail the components of SRL at each level of creative mathematical thinking. This study uses an explanatory sequential combination research design. The study population was high school students at SMAN 3 Klaten. The sampling technique used in this study is simple random sampling. The research sample measured mathematical creative thinking ability ( Y ) as a dependent variable, and SRL consists of three components, namely metacognition ( X1 ), motivation ( X2 ), and behavioristic ( X3 ). At the same time, the research subject selection technique is purposive sampling. The researcher chose to divide students' mathematical creative thinking skills into three levels: high, medium, low, where in each level was selected three research subjects. SRL has a positive effect on the ability to think mathematically creative by 85.4%. Metacognitive has the strongest influence on mathematical creative thinking skills. The SRL component has a role in every aspect of creative mathematical thinking consisting of fluency, flexibility, elaboration, and originality. Therefore, for improving mathematical creative thinking skills, students should be given learning based on SRL. Resumo A maioria dos indivíduos entende o pensamento criativo matemático não apenas como um fator cognitivo, mas também como um fator afetivo. A aprendizagem autorregulada (SRL) é considerada um fator afetivo que influencia a capacidade de pensamento criativo matemático. O objetivo deste estudo é determinar o efeito do SRL na capacidade de pensamento criativo matemático e analisar em detalhes os componentes do SRL em cada nível do pensamento criativo matemático a partir de um projeto de pesquisa de combinação sequencial explicativa. A população do estudo foi composta por alunos do ensino médio da SMAN 3 Klaten. A técnica de amostragem usada neste estudo é a amostragem aleatória simples. A amostra da pesquisa mediu a capacidade de pensamento criativo matemático ( Y ) como uma variável dependente e o SRL consiste em três componentes, a saber, metacognitivo ( X1 ), motivação ( X2 ) e comportamental ( X3 ), sendo que a técnica de seleção de sujeitos de pesquisa é a amostragem proposital. Metacognitivo tem a maior influência nas habilidades de pensamento criativo matemático. A pesquisadora optou por dividir as habilidades de pensamento criativo matemático dos alunos em três níveis, a saber, alto, médio e baixo, de forma que, para cada nível, foram selecionados três sujeitos de pesquisa. SRL tem um efeito positivo de 85,4% sobre a capacidade de pensar criativo matematicamente. O componente SRL tem uma função em todos os aspectos do pensamento criativo matemático, consistindo em: fluência, flexibilidade, elaboração e originalidade. Portanto, para melhorar as habilidades de pensamento criativo matemático, os alunos devem receber um aprendizado baseado no SRL.